2016
DOI: 10.1186/s40557-016-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shift work on abdominal obesity among 20–39-year-old female nurses: a 5-year retrospective longitudinal study

Abstract: BackgroundThis study aimed to investigate the effects of shift work on abdominal obesity among young and middle-aged female nurses during a 5-year retrospective study.MethodsThis retrospective study included female nurses (20–39 years old) who worked at a university hospital in Korea and had available health screening results from 2010–2015. Among 2,611 employees, 934 healthy 20–39-year-old female nurses were identified, and data regarding their demographic information (age and date of employment), waist circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Ten studies found an increased risk of obesity from rotating shift work; three studies reported an increased risk from permanent night work, but only one study reported an increased risk from irregular shift work. Moreover, Bushnell et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies found an increased risk of obesity from rotating shift work; three studies reported an increased risk from permanent night work, but only one study reported an increased risk from irregular shift work. Moreover, Bushnell et al .…”
Section: Resultsmentioning
confidence: 99%
“…Six articles reported results with occupationally mixed populations. Eleven studies focused on female workers, and five focused on male participants. Twelve studies included participants of both genders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Night shift work is associated with an increase in BMI and can lead to overweight and obesity [11][12][13][14][15][16]. Cumulative night shift work is strongly related to an increase in BMI, waist circumference [17][18][19], hip circumference and waist to hip ratio [20]. Weight gain associated with night shift work may be the result of an excess of calorie intake and a lack of physical activity during night [21,22].…”
Section: Introductionmentioning
confidence: 99%